Police misconduct in Russia: history and contemporaneity - Aleksandrovich, Fatyanov Aleksey; Alekseevna, Lakhtina Tatyana; Aladdinovna, Alieva Gyunay (Opción, 2019)
The present paper focuses on the analysis of issues that arise in terms of theory and law enforcement practice. The key approach to the study of this problem is based on the distinctive difference between administrative and criminal offenses. The paper deals with the issues connected with the preventative activity of law-enforcement authorities of the Russian Federation. It reviews the doctrinal approach to the topic under consideration. The paper appeals to executors of law, students, and candidates for a master’s degree and postgraduates in the field of study “Jurisprudence”.